Analysis of histone deacetylation as an epigenetic factor in somaclonal variation of Ananas comosus variety MD2 / Nur Asniyati Abdul Halim - Nur Asniyati , Abdul Halim (2018)
The removal of acetyl groups (O=C-CH3) from ε-N-acetyl lysine amino acid on histone tails (histone deacetylation) plays a significant role for plants in response to stress conditions, leading to epigenetic modification related to somaclonal variation phenomenon. In spite of its importance, information about histone deacetylation activities in major tropical crops, such as pineapple (Ananas comosus variety MD2), remains obscure. Therefore, the main aim of this study was to investigate the changes of deacetylation in response to abiotic stresses in pineapple. Leaf base of the A. comosus var. MD2 was used as explants for shoot initiation. The regenerated plantlets were then used to create somaclonal variants. In this study, optimum regeneration media (OM) with the highest number of microshoots (6 ± 0.4) produced from leaf bases was Murashige and Skoog (MS) medium supplemented with 1.0 mg L-1 indole-3-butyric acid (IBA) and 2.0 mg L-1 6-benzylaminopurine (BAP). Somaclonal variants were induced from in vitro A. comosus through hormonal induction, NaCl, and abscisic acid (ABA) supplementation. Dwarfism was observed in regeneration media (RM) containing either 2.0 mg L-1 IBA and 4.0 mg L-1 BAP, 1.0 % (w/v) NaCl or 1.0 mg L-1 ABA. The histone deacetylase (HDAC) enzyme activity for dwarf and non-dwarf plantlets was also analyzed. The highest HDAC activity (109,333.33 ± 4.40 ng/min/mg) was recorded for dwarf plantlets grown on RM supplemented with 1.0 mg L-1 ABA. The dwarf variants underwent phenotypic recovery within 8 months after transferred to MS basal medium. No ploidy alteration was detected in these dwarf plantlets by a flow cytometry. The relative expression level of endogenous Ananas comosus histone deacetylase gene (AcHD2) was also evaluated to determine the transcripts level among the plantlets. Data analysis showed that the expression level of AcHD2 in the variants grown on RM 1.0 % (w/v) NaCl and RM supplemented with 1.0 mg L-1 ABA were higher compared to phenotypically normal plantlets grown on MS basal media and optimum regeneration media (OM). To confirm the dwarfism is caused by epigenetic modification, AtHD2 gene from Arabidopsis thaliana was synthesized and expressed in A. comosus. Morphological observation of the transgenic based on its height shows significant reduction (dwarf) as compared to the wild type. The histone deacetylase (HDAC) enzyme activity for the transgenic is also higher (5,902.00 ± 25.10 ng/min/mg) compared to the wild type (666.67 ± 22.07 ng/min/mg). Ploidy evaluation of transgenic shows no change occurred in the sample and remained as 2n. The relative expression level of AtHD2 in the transgenic plant was higher compared to the wild type plants. These evidences have supported the results of the incidence of somaclonal variation in the media after treated with different abiotic stresses. Collectively, these results depict the histone deacetylation activities in A. comosus and implied that the incidence of somaclonal variation in response to abiotic stress in A. comosus was epigenetically regulated.